A study on Bridging Chemical Transformation and Climate Feedbacks in the Earth System - Heena T. Shaikh; IR. Dr. Kazi Kutubuddin Sayyad Liyakat (International Journal of Climate Conditions, 2026)
The atmosphere operates as a vast and complex chemical reactor, where minute-scale transformations exert profound influence on planetary-scale climate stability. This research investigates the multi-scale coupling between reactive tropospheric chemistry and large-scale climate feedbacks, challenging traditional modeling approaches that often divorce chemical kinetics from dynamic processes. By integrating high-resolution chemical transport models (CTMs) with comprehensive Earth System Models (ESMs), we map the flow of energy and matter from the molecular initiation of photochemistry to global radiative forcing. We demonstrate that the sensitivity of the tropospheric oxidant budget—driven by the concentration of hydroxyl radical (OH) and ozone—is critically modulated by evolving biogenic volatile organic compound (BVOC) emissions and aerosol composition. Crucially, the study identifies a dominant positive feedback loop: regional warming enhances BVOC emissions, which increases secondary organic aerosol (SOA) nucleation, leading to significant alterations in cloud condensation nuclei (CCN) population and subsequent cloud albedo. While this chemical-aerosol pathway exerts a net cooling tendency locally, the concurrent chemical lifetime reduction of potent greenhouse gases (GHGs) like methane introduces a competing warming effect at the global scale. This analysis underscores the inherent fragility of the atmospheric system and emphasizes that accurate climate projections fundamentally rely on resolving the non-linear coupling processes that bridge the micro-scale crucible of reactivity with macro-scale climate dynamics. Here we present the review of the system.
Keywords: BVOC; CCN; Chemical Transformation; Earth System; climate feedbacks